Reinforcement of Students' Entrepreneurial Intentions through Soft Skills and Hard Skills Empowerment - Mardikaningsih, Rahayu (Metromedia, 2022)
Entrepreneurship patterns and trends continue to change according to the times and technological sophistication so that becoming an entrepreneur does not only have to be able to master entrepreneurship in the form of hard skills, but more than that, you must also master soft skills. Disruption is an era of innovation and massive change that fundamentally changes all existing systems, arrangements, and landscapes in new ways. The role of soft skills in every student is very necessary to face the disruptions that occur in order to prepare themselves for entrepreneurship after graduation. Hard skills are a must for students and soft skills are very important in entrepreneurship. Soft skills can be improved in several ways, namely; responsible, committed, willing to take risks, and action oriented. The role of soft skills to strengthen the entrepreneurial spirit for prospective undergraduates in the era of disruption. The role of universities is very necessary in this regard. In Higher Education, one of the strategies to develop an entrepreneurial spirit is to build an ecosystem for budding entrepreneurs and develop a number of financing schemes or funding for entrepreneurial activities.